2021
DOI: 10.1093/ageing/afab024
|View full text |Cite
|
Sign up to set email alerts
|

Reasons for discontinuing oral anticoagulation therapy for atrial fibrillation: a systematic review

Abstract: Introduction Atrial fibrillation (AF) is the most common cardiac arrhythmia and can lead to significant comorbidities and mortality. Persistence with oral anticoagulation (OAC) is crucial to prevent stroke but rates of discontinuation are high. This systematic review explored underlying reasons for OAC discontinuation. Methods A systematic review was undertaken to identify studies that reported factors influencing discontinua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 29 publications
(100 reference statements)
0
25
0
Order By: Relevance
“…Several previous studies also reported a higher rate of warfarin discontinuation compared to each DOAC [ 30 ]. This could be related to either incident bleeding events or anticipated higher risk of bleeding with warfarin or the risk of frailty in the elderly [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies also reported a higher rate of warfarin discontinuation compared to each DOAC [ 30 ]. This could be related to either incident bleeding events or anticipated higher risk of bleeding with warfarin or the risk of frailty in the elderly [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…21 Additionally, frailty is a major factor influencing discontinuation of therapy for those already taking anticoagulants. 22 Such findings illustrate the perpetual dilemma for prescribing anticoagulation in co-existent atrial fibrillation, frailty, and risk of falls, particularly given the rising rateadjusted fall death rate as more individuals are surviving with stroke disability. 23 Frailty and the risk of stroke Frailty in stroke is common.…”
Section: Frailty and Vascular Risk Factorsmentioning
confidence: 98%
“…The most common outcomes reported were TTR, proportion of INR measurements in range, or PDC (a measure used for direct OACs as they do not require as frequent blood monitoring as warfarin). Adherence [50,57,59,60], persistence [52,56], discontinuation [51], and switching [58] were also reported. Most reviews assessed patients with any condition (including AF or VTE); nine reviews focussed on patients with AF; one focussed on AF or VTE; none focussed on patients with VTE.…”
Section: Self-monitoringmentioning
confidence: 98%
“…From the initial search, we identified six reviews [44][45][46][47][48][49] that addressed self-monitoring, and from the update search, a further 15 reviews [38,[50][51][52][53][54][55][56][57][58][59][60][61][62][63] that addressed self-monitoring or adherence. The summary characteristics are presented in Table 3, below.…”
Section: Self-monitoringmentioning
confidence: 99%